Journal of Polymer Engineering (De Gruyter, 1984)
Journal of Polymer Engineering publishes reviews, original basic and applied research contributions as well as recent technological developments in polymer engineering. Polymer engineering is a strongly interdisciplinary field and papers published by the journal may span areas such as polymer physics, polymer processing and engineering of polymer-based materials and their applications.